KOSMOS 2020 Peru mesocosm study on ecosystem responses to different light and upwelling intensities: CTD data - Antonia Thielecke; Andrea Ludwig; Ulf Riebesell (PANGAEA, 2023)
This data is part of the BMBF project CUSCO (Coastal Upwelling Systems in a Changing Ocean). Here we report the environmental conditions during a 35-day experiment, where we enclosed natural plankton communities in in-situ mesocosms off Peru. The experiment investigated the interactive effects of light and upwelling on the Humboldt upwelling ecosystem by mimicking a gradient of upwelling intensities (0%, 15%, 30%, 45% and 60%) under summer-time high light and winter-time low light. CTD casts were taken between 0 and 12.5m with a CTD167M sensor system (Sea&Sun Technology, Trappenkamp, Germany) to generate depth profiles of conductivity, salinity, density, pH, temperature and photosynthetically active radiation (PAR) as well as oxygen, hydrogen sulphide and Chla concentrations (sensors described in (Schulz and Riebesell, 2013; Bach et al., 2016; doi:10.1007/s00227-012-1965-y, doi:10.1002/2016GB005372). The water sampling and CTD casts of the Pacific took place in the mesocosm field.